Monitoring of drinking water quality in Mladenovac in the period 2021–2023 - Pakić, Snežana; Avramović, Dušan; Slepčević, Vesna; Vojvodić, Kristina; Pejović, Janko; Mršulja, Ana (PONS - medicinski časopis, 2026)
Introduction Water is of great importance for the entire living world. The World Health Organization classified water supply and drinking water quality among twelve basic indicators of the health status of a country's population. Aim The aim of the work is the analysis of physico-chemical and microbiological tests of drinking water in the territory of Mladenovac in a three-year period (2021-2023). Materials and methodsThe method of work is analytical-descriptive. For the analysis of the water quality in Mladenovac, data from the Annual Reports on the health control of drinking water from the water supply in Mladenovac for the years 2021, 2022 and 2023 were used. In the Laboratories of the City Public Health Institute of Belgrade, physico-chemical and microbiological tests of drinking water samples are carried out in the scope of Basic and Periodic analyzes according to the Rulebook on the hygienic suitability of drinking water ("Official Gazette of the FRY" No. 42/98 and 44/99 and "Official Gazette of the RS" No. 28/2019). ResultsThe results of laboratory tests of water conducted in 2021 showed that out of a total of 362 tested samples, 292 (80.66%) were physically and chemically defective, while 51 (14.09%) were microbiologically defective. In 2022, a total of 368 samples were tested. From a physico-chemical point of view, 311 (84.51%) samples were unhealthy (unsafe), 50 (13.59%) were microbiologically unhealthy. Out of a total of 385 water samples tested in 2023, 273 (70.91%) were physico-chemically defective, and 43 (11.14%) were microbiologically defective. The causes of failure are physico-chemical parameters: turbidity, iron, manganese, ammonia and nitrites. In terms of microbiological water quality, the cause of malfunction is an increased total number of aerobic mesophilic bacteria in 1 ml of water, the presence of total coliform bacteria, Pseudomonas aeruginosa, faecal streptococci. ConclusionAnalyzes indicate the need for urgent improvement of the water supply situation. Measures should be taken to reduce microbiological contamination and to reduce iron and manganese concentrations and water turbidity.
Keywords: Key words: health safety of drinking water, samples, water supply.